2022
DOI: 10.3390/rs15010208
|View full text |Cite
|
Sign up to set email alerts
|

Ground Surface Freezing and Thawing Index Distribution in the Qinghai-Tibet Engineering Corridor and Factors Analysis Based on GeoDetector Technique

Abstract: The land surface temperature obtained from remote sensing was widely used in the simulation of permafrost mapping instead of air temperature with the rapid development of remote sensing technology. The land surface freezing and thawing index (LFI and LTI), which is commonly regarded as the ground surface freezing and thawing index (GFI and GTI), can produce certain errors in the simulation of permafrost distribution on the Qinghai–Tibet Plateau. This paper improved the accuracy of the thermal condition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
2
1
Order By: Relevance
“…We consider that this may be because the spatial distribution of soil types is characterized by latitudinal zonation [69], but the NCPZ has a small latitudinal span and a relatively homogeneous type of soil spatial distribution. In addition, Lloyd et al [70], in studying the relationship between soil freezing and soil moisture in Alaska, USA, found that the relationship was not significant, which was different from the results of our study and that of Ma et al [71], which may be due to the differences in the study area and climate. The high latitude of Alaska, USA, is cold year-round, while the warmer climate of the NCPZ makes GSTs susceptible to a variety of factors.…”
Section: Sfds and Influencing Factorscontrasting
confidence: 99%
“…We consider that this may be because the spatial distribution of soil types is characterized by latitudinal zonation [69], but the NCPZ has a small latitudinal span and a relatively homogeneous type of soil spatial distribution. In addition, Lloyd et al [70], in studying the relationship between soil freezing and soil moisture in Alaska, USA, found that the relationship was not significant, which was different from the results of our study and that of Ma et al [71], which may be due to the differences in the study area and climate. The high latitude of Alaska, USA, is cold year-round, while the warmer climate of the NCPZ makes GSTs susceptible to a variety of factors.…”
Section: Sfds and Influencing Factorscontrasting
confidence: 99%
“…The definition of the QTEC lacks clarity and is often understood as the area along the QTH or QTR within a certain range, or a combination of both within a specific boundary. The boundary distance is a subject of debate, with values such as 5 km, 10 km, and 20 km being commonly used [6,7,53]. This area is typically classified as a buffer zone.…”
Section: Study Area Overviewmentioning
confidence: 99%
“…The freezing (thawing) index represents the cumulative sum of temperatures below (above) 0 • C during a freezing (thawing) period [32][33][34]. To maintain the continuity of the freezing period, we defined the freezing period from 1 July of one year to 30 June of the following year.…”
Section: Freezing-thawing Indexmentioning
confidence: 99%